Omaveloxolone and TX63682 are hepatoprotective in the STAM mouse model of nonalcoholic steatohepatitis. Issue 9 (14th May 2020) - Reisman, Scott A.; Ferguson, Deborah A.; Lee, Chun‐Yue I.; Proksch, Joel W.
Abstract: Omaveloxolone is a potent activator of Nrf2, a master transcriptional regulator of a multitude of cytoprotective functions, including antioxidative, anti‐inflammatory, and mitochondrial bioenergetic effects. Some of the most potent known effects of Nrf2 involve hepatoprotective functions. The purpose of this study was to evaluate the effects of omaveloxolone and TX63682, a closely related structural analog with similar oral bioavailability, in the STAM mouse model of nonalcoholic steatohepatitis (NASH). C57Bl/6 mice received a single subcutaneous injection of streptozotocin two days after birth and were fed a high‐fat diet from 4 to 9 weeks of age. Omaveloxolone and TX63682 were orally administered at doses of 1, 3, and 10 mg/kg/d from 6 to 9 weeks of age. Consistent with the beneficial effects of Nrf2 on hepatoprotection and improved lipid handling, both omaveloxolone and TX63682 decreased hepatic fat deposition, hepatocellular ballooning, inflammatory cell infiltration, and collagen deposition. Omaveloxolone and TX63682 also improved blood glucose control, as evidenced by reductions in nonfasting blood glucose and glycated hemoglobin A1C concentrations. Reductions in liver and serum triglycerides with omaveloxolone and TX63682 treatment were also observed. Both omaveloxolone and TX63682 decreased leptin and increased adiponectin in serum, which is consistent with the anti‐inflammatory and antifibrotic effects observed in the liver. These results were associated with significant induction of Nrf2 target gene expression in the liver, including NAD(P)H:quinone oxidoreductase 1, sulfiredoxin 1, and ferritin heavy chain 1. Overall, these data suggest that omaveloxolone and related Nrf2 activators may be useful for the treatment of NASH.